Graph Transformation Model of a Triangulated Network of Mobile Units - Gruner, Stefan (Electronic Communications of the EASST, 2008)
A triangulated network of mobile units is modelled by means of a graph trans-formation system in which graph nodes are labelled with geometric coordinates and edges are labelled with distances. Nodes represent mobile units and edges represent wireless radio communication links between them. Under concurrency the model can describe interesting practical scenarios, for example swarms of taxis in an urban environment. The contribution features the enhancement of a graph transformation system by trigonometric calculations. By the way it is also shown that the classical negative edge condition has only limited applicability if a strict locality principle is assumed, and "vice versa" that there are reasonable modeling cases in which this locality principle itself fails to suffice.